The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1808-1657000452017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant protection products on Rhynchophorus palmarum L. (Coleoptera: Curculionidae) larvae in laboratory

Abstract: With the aim of developing tools for simultaneously managing Rhynchophorus palmarum and the coconut stem bleeding disease, we evaluated the effects of the insecticide thiamethoxam and the fungicide cyproconazole on R. palmarum larvae under laboratory conditions. Early-instar and intermediate-instar larvae were fed on an artificial diet containing 0.1% concentration of insecticide, fungicide or a mixture of both. Larval mortality was assessed daily during the 48 hours after the application of the treatments. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…In this sense, exposure time to synthetic insecticides is likely shorter in individuals with wider pronotum. In accordance with this, some studies have reported that this pest can prevail in agricultural areas with high intensity of insecticide use [75]. This is related to the prediction that agricultural intensification can create insect pests from herbivores, which illustrates that frequent insecticide use provides conditions permissive or conducive to the emergence and spread of pests [3,8].…”
Section: Discussionmentioning
confidence: 53%
“…In this sense, exposure time to synthetic insecticides is likely shorter in individuals with wider pronotum. In accordance with this, some studies have reported that this pest can prevail in agricultural areas with high intensity of insecticide use [75]. This is related to the prediction that agricultural intensification can create insect pests from herbivores, which illustrates that frequent insecticide use provides conditions permissive or conducive to the emergence and spread of pests [3,8].…”
Section: Discussionmentioning
confidence: 53%
“…Em estudo similar, Chihaoui-Meridja et al (2019) observaram que adultos de Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) alimentados com dieta natural (maçã) tratada com o produto à base de tiametoxam (Renova 250 ® WG) na dose equivalente a 0,2 mL do p.c./inseto, tiveram mortalidade de 50% após 5 dias de exposição ao produto. Avaliando a mortalidade das larvas de R. palmarum alimentadas com dieta artificial contendo tiametoxam incorporado, Santos et al (2018) constataram que, na menor concentração (0,1% de i.a., equivalente a 1.000 ppm), o inseticida causou 100% de mortalidade nas larvas pequenas e 90% em larvas de tamanho intermediário, as quais apresentaram os mesmos sintomas verificados nos adultos do presente trabalho, após 48 horas. Ao compararmos ambos os estudos, fica evidenciado que as doses avaliadas por Santos et al (2018) estão além do espectro de letalidade capaz de determinar com maior precisão as doses letais (CL 50 e CL 90 ), como observado para adultos desta praga, observados no presente estudo.…”
Section: Resultsunclassified
“…Avaliando a mortalidade das larvas de R. palmarum alimentadas com dieta artificial contendo tiametoxam incorporado, Santos et al (2018) constataram que, na menor concentração (0,1% de i.a., equivalente a 1.000 ppm), o inseticida causou 100% de mortalidade nas larvas pequenas e 90% em larvas de tamanho intermediário, as quais apresentaram os mesmos sintomas verificados nos adultos do presente trabalho, após 48 horas. Ao compararmos ambos os estudos, fica evidenciado que as doses avaliadas por Santos et al (2018) estão além do espectro de letalidade capaz de determinar com maior precisão as doses letais (CL 50 e CL 90 ), como observado para adultos desta praga, observados no presente estudo. Assim, estudos futuros para determinação das doses letais para larvas desta praga são essenciais para melhor dimensionamento da aplicação deste inseticida a fim de otimizar o uso deste método de controle em possíveis aplicações em campo.…”
Section: Resultsunclassified
“…Chemical control of APW with carbaryl, carbofuran, imidacloprid, abamectin, deltamethrin, fipronil, spinosad and phenylpyrazole often is not fruitful (Al-Dosary et al, 2013;Dos Santos et al, 2018;Martinez et al, 2019). The application of entomopathogenic fungi, such as Metarhizium anisopliae (Metschn.)…”
Section: Introductionmentioning
confidence: 99%